2022
DOI: 10.3389/fpsyg.2022.809513
|View full text |Cite
|
Sign up to set email alerts
|

Apology and Its Acceptance: Perceived Reconciliatory Attitudes Reduce Outgroup Dehumanization

Abstract: Based on real-life intergroup animosities originating from a historical conflict, the current study examined how the perceived stance of the outgroup about the conflict affects the dehumanization of the outgroup. In Study 1 (N = 120), Korean undergraduates attributed more human nature to the Japanese after reading an article that the Japanese government did (vs. refused to) issue an official apology for a historical wrong. In turn, the more human nature assigned to the Japanese predicted higher expectations ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…These results provide an important, ecologically valid extension of prior work pointing to the centrality of morality in perceptions of humanity (Brandt & Reyna, 2011;Phillips, 2022;Schwartz & Struch, 1989) and suggesting that highlighting a target's moral agency or remorse can (re)humanize them (Borinca et al, 2021;Jin et al, 2022;Khamitov et al, 2016). Whereas that research was theoretical or used relatively contrived paradigms (e.g., experimenter-created vignettes; Khamitov et al, 2016), we drew on it to develop an intervention with real media content that reduced support for war crimes during an emotionally charged military attackdemonstrating the promise of applying insights from basic dehumanization research to promote peace (see also .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These results provide an important, ecologically valid extension of prior work pointing to the centrality of morality in perceptions of humanity (Brandt & Reyna, 2011;Phillips, 2022;Schwartz & Struch, 1989) and suggesting that highlighting a target's moral agency or remorse can (re)humanize them (Borinca et al, 2021;Jin et al, 2022;Khamitov et al, 2016). Whereas that research was theoretical or used relatively contrived paradigms (e.g., experimenter-created vignettes; Khamitov et al, 2016), we drew on it to develop an intervention with real media content that reduced support for war crimes during an emotionally charged military attackdemonstrating the promise of applying insights from basic dehumanization research to promote peace (see also .…”
Section: Discussionsupporting
confidence: 77%
“…Although perpetrators of egregious harm are often denied an essentially human moral compass (Kelman, 1973;Phillips, 2022), their expressions of moral agency or remorse can (re)humanize them (Borinca et al, 2021;Jin et al, 2022;Khamitov et al, 2016). Therefore, we aimed to expose Americans to Russian soldiers' essentially human moral qualities following the invasion.…”
Section: Developing a Humanization Interventionmentioning
confidence: 99%
“…Similarly, Jin et al. (2022) reported that Korean participants being informed that the Japanese government did issue an official apology for a historical wrong, and Japanese participants being informed that an official apology for a historical wrong from Japan was accepted by Koreans, resulted in the reduction of mutual dehumanization and improved positive intergroup relations. It seems that at least in some cases, cultural factors can differentially affect how apologies are received.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the issuance of intergroup apologies was associated with lower perceived remorse towards the outgroup only among Korean participants; no significant effect of intergroup apology on perceived remorse was found among their American participants. Similarly, Jin et al (2022) reported that Korean participants being informed that the Japanese government did issue an official apology for a historical wrong, and Japanese participants being informed that an official apology for a historical wrong from Japan was accepted by Koreans, resulted in the reduction of mutual dehumanization and improved positive intergroup relations. It seems that at least in some cases, cultural factors can differentially affect how apologies are received.…”
Section: Apology Mismatchmentioning
confidence: 99%
“…To do so, we leveraged the rich media content at our fingertips by searching open-access online repositories (e.g., YouTube, Vimeo) for videos that humanized Russian soldiers. We identified six videos we believed would humanize Russian soldiers by individuating them 54,63,64 , highlighting their moral agency through their opposition to the invasion 42,65,66 , and revealing their remorse for their participation in it 53,67,68 .…”
Section: Studymentioning
confidence: 99%